Political Configuration of Islamic Law in Legal Development in Indonesia - Sanusi, Nur Taufiq; Fauzan, Ahmad; Syatar, Abdul; Kurniati, Kurniati; Hasim, Hasanuddin (Jurnal Adabiyah, 2023)
Indonesia's multicultural society influences legal policy in the development of the country from philosophical, cultural, social, and religious aspects. The current development of customary law, commonly referred to as al-dah al-muhakkamah, strongly supports national law as a source of law and is used by the Indonesian Islamic community along with customary law as its legal basis. Both are designed to provide legal benefits for the Indonesian people. This study focuses on the synchronization of Islamic law and national law to create a national law that is in harmony with the existing law in society through normative legal investigation methods and comparative legal approaches. The method used is qualitative method. The procedural model is a research technique that gathers verbal or written descriptions from sources in order to apply normative comparison techniques. The research results show Islamic law in the development of national law is the answer to the democratization of various sources of law in Indonesia. That is, national sources of law need to pay attention to the basic philosophy of Islamic law, which can answer and solve substantive and formal legal problems as the basis for the development of national law. The formalization of Islamic law in the context of the policy development of law or the development of Islamic law (legal structure) in the development of national law is not sufficiently limited to mere formalization but to its nature and content. امللخص يؤثر المجتمع متعدد الثقافات في إندونيسيا على السياسة القانونية في تطور البلاد من الجوانب الفلسفية والثقافية والاجتماعية والدينية. إن تطوير القانون العرفي الذي يشار إليه عادة باسم "العدة المحكمة" يدعم اليوم بقوة القانون الوطني كمصدر للقانون ويستخدمه المجتمع الإسلامي الإندونيسي جنبًا إلى جنب مع القانون العرفي كأساس قانوني له. كلاهما مصمم لتقديم مزايا قانونية لشعب إندونيسيا. يركز هذا البحث على تزامن الشريعة الإسلامية والقانون الوطني لتحقيق القانون الوطني المتوافق مع القوانين القائمة في المجتمع من خلال أساليب التحقيق القانوني المعياري والأساليب القانونية المقارنة. الطريقة المستخدمة هي طريقة نوعية. تقنيات جمع البيانات ، وهي جمع الأوصاف الشفوية أو المكتوبة من عدة مصادر كمواد مقارنة معيارية. تظهر نتائج البحث أن الشريعة الإسلامية في تطوير القانون الوطني هي الرد على دمقرطة مصادر القانون المختلفة في إندونيسيا. وهذا يعني أن مصادر القانون الوطني بحاجة إلى الاهتمام بالفلسفة الأساسية للشريعة الإسلامية التي يمكنها الإجابة على المشكلات القانونية الموضوعية والشكلية وحلها كأساس لتطوير القانون الوطني. إن إضفاء الطابع الرسمي على الشريعة الإسلامية في سياق سياسات تطوير القانون أو تطوير الشريعة الإسلامية (الهيكل القانوني) في تطوير القانون الوطني لا يقتصر بشكل كافٍ على مجرد إضفاء الطابع الرسمي ، ولكن ما هو جوهرها ومحتواها. الكلمات المفتاحية: التكوين السياسي ، التطور القانوني ، السياسة القانونية ، الشريعة الإسلامية Abstrak Masyarakat multikultural Indonesia mempengaruhi kebijakan hukum dalam pembangunan negara dari aspek filosofis, budaya, sosial dan agama. Perkembangan hukum adat yang biasa disebut dengan al-ādah al-muhakkamah dewasa ini sangat mendukung hukum nasional sebagai sumber hukum dan digunakan oleh masyarakat Islam Indonesia bersama dengan hukum adat sebagai landasan hukumnya. Keduanya dirancang untuk memberikan manfaat hukum bagi masyarakat Indonesia. Penelitian ini menitikberatkan pada sinkronisasi hukum Islam dan hukum nasional untuk mewujudkan hukum nasional yang selaras dengan hukum yang ada di masyarakat melalui metode penyelidikan hukum normatif dan pendekatan hukum komparatif. Metode yang digunakan adalah metode qualitatif. Teknik pengumpulan data yaitu mengumpulkan deskripsi verbal atau tertulis dari beberapa sumber sebagai bahan perbandingan normatif. Hasil penelitian menunjukkan bahwa Hukum Islam dalam pembangunan hukum nasional merupakan jawaban atas demokratisasi berbagai sumber hukum di Indonesia. Artinya, sumber hukum nasional perlu memperhatikan filosofi dasar hukum Islam yang dapat menjawab dan memecahkan masalah hukum substantif dan formal sebagai landasan pembangunan hukum nasional. Formalisasi hukum Islam dalam konteks kebijakan pembangunan hukum atau pembangunan hukum Islam (legal structure) dalam pembangunan hukum nasional tidak cukup terbatas pada formalisasi belaka, tetapi bagaimana hakikat dan isinya. Kata Kunci: Konfigurasi politik; Pembangunan hukum; Politik hukum; Hukum Islam